Effect of Drip Irrigation on Water-use Efficiency and Productivity of Castor - Singh Chawara, R S; Kaushish, Sandeep (Annals of Arid Zone, 2016)
The field experiment was conducted to see effects of drip irrigation system on water-use efficiency and productivity of castor grown on light textured soils of Western Rajasthan. The treatments comprising of four levels of irrigation viz., 0.8V, 1.0V and 1.2V (volume/plant/day worked out on ET basis) and check basin system were compared in RBD with six replications. Results revealed that application of irrigation water at 1.0 unit volume through in-line drippers gave maximum seed yield of 4085 kg ha-1 which was significantly higher over 0.8V and check basin system by 682 and 497 kg ha-1, respectively. Irrigation at 1.0 unit volume increased net return and water-use efficiency by Rs. 5,197 ha-1 and 5 kg mm-1 ha-1, respectively, compared to check basin system with 31.2% saving of water. Key words: Drip irrigation, castor, seed yield, water-use efficiency, economics.